Small-rotative fixed-target serial synchrotron crystallography (SR-FT-SSX) for molecular crystals - Sam G. Lewis; Ben A. Coulson; Anna J. Warren; Mark R. Warren; Lauren E. Hatcher (Communications Chemistry)
Abstract The increasing availability of ultrabright Light Sources is facilitating the study of smaller crystals at faster timescales but with an increased risk of severe X-ray damage, leading to developments in multi-crystal methods such as serial crystallography (SX). SX studies on crystals with small unit cells are challenging as very few reflections are recorded in a single data image, making it difficult to determine the orientation matrix for each crystal and thus preventing the combination of the data from all crystals for structure solution. We herein present a Small-Rotative Fixed-Target Serial Synchrotron Crystallography (SR-FT-SSX) methodology, in which rotation of the serial target through a small diffraction angle $$(φ )$$ ( φ ) at each crystal delivers high-quality data, facilitating ab initio unit cell determination and atomic-scale structure solution. The method is benchmarked using microcrystals of the small-molecule photoswitch sodium nitroprusside dihydrate, obtaining complete data to d min = 0.6 Å by combining just 66 partial datasets selected against rigorous quality criteria.